The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1086/341408
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of HumanCalicivirusInfection: A Prospective Cohort Study

Abstract: We investigated the natural history of human Calicivirus infection in the community. Clinical information was obtained from 99 subjects infected with Norwalk-like viruses (NLV) and 40 subjects infected with Sapporo-like viruses (SLV) in a prospective, community-based cohort study. NLV infection was common in all age groups, whereas SLV infection was mainly restricted to children aged <5 years. Symptoms lasted for a median of 5 and 6 days for NLV and SLV infections, respectively. Disease was characterized by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
311
4
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(354 citation statements)
references
References 39 publications
25
311
4
14
Order By: Relevance
“…The average number of hospitalization days for NoV and RV infections was similar for both in this study, close to five days, as also reported by Rockx et al (2002) in a prospective study about the natural history of calicivirus infection. The duration of NoV infection was previously determined to be short (1-3 days); however, reports of sporadic cases have shown longer periods (Atmar & Estes 2006).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The average number of hospitalization days for NoV and RV infections was similar for both in this study, close to five days, as also reported by Rockx et al (2002) in a prospective study about the natural history of calicivirus infection. The duration of NoV infection was previously determined to be short (1-3 days); however, reports of sporadic cases have shown longer periods (Atmar & Estes 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Clinical reports describe vomit as an important manifestation for both RV and NoV infection, but less than we observed (Estes et al 2001, Kapikian et al 2001, Rockx et al 2002. While Rockx et al (2002) described that vomit was less common in NoV-infected children aged < 1 year (59%), 85.7% of the patients in the present study, also infected with NoV at this same age group, presented vomit. Our results are also in contrast with those reported in children infected with NoV at a hospital in Rio de Janeiro that reported vomit in 33.3% of the cases (Victoria et al 2007).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Detection of fecal virus shedding was short (1 to 4 days by RT-PCR, but longer by amplicon hybridization, through PID 8). Longer asymptomatic shedding has been described in some normal humans, where 28% of infected individuals shed virus for up to 3 weeks after the onset of disease (38). Similar results were observed in a trial involving pigtail macaques inoculated with Toronto virus (HuNoV GII/3) (45).…”
Section: Discussionsupporting
confidence: 68%
“…Sapoviruses have been associated with diarrhoea (95% of patients) and vomiting (60% of patients), with clinical symptoms lasting a median of six days in community-based studies in the Netherlands [18]. However, SaVs have also been associated with asymptomatic infections and were detected in 28.6% (16/56) of children in a day-care study in Brazil [19].…”
Section: Introductionmentioning
confidence: 99%